2018
DOI: 10.1039/c8ta01570h
|View full text |Cite
|
Sign up to set email alerts
|

SiOC nanolayer wrapped 3D interconnected graphene sponge as a high-performance anode for lithium ion batteries

Abstract: A SiOC nanolayer wrapped 3D interconnected GNS conductive framework contributed to the best ever reported high-performance for SiOC-based anode materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 54 publications
2
40
0
Order By: Relevance
“…In terms of composition, PDCs with increased free carbon have been designed through control of pyrolysis conditions 38 and the use of carbonrich precursors or cross-linkers [39][40] . Composite materials incorporating carbon nanostructures (CNTs 41 or graphene 37,[42][43][44] ) and /or nanoparticles of Sn 18,23 , Sb 19,45 , or Si 10,20…”
Section: Introductionmentioning
confidence: 99%
“…In terms of composition, PDCs with increased free carbon have been designed through control of pyrolysis conditions 38 and the use of carbonrich precursors or cross-linkers [39][40] . Composite materials incorporating carbon nanostructures (CNTs 41 or graphene 37,[42][43][44] ) and /or nanoparticles of Sn 18,23 , Sb 19,45 , or Si 10,20…”
Section: Introductionmentioning
confidence: 99%
“…Such ICE is higher than many recently reported SiO x anodes. 17,19,20,22,23,28 Fig. 3c displays the typical charge-discharge curves of SiO x / NC-2 at 0.1-3.2 A g À1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3f compares the rate performance of SiO x /NC-2 and many reported SiO x /C composites with x values close to 1.5. [17][18][19][20][21][22][23][24][25][26][27] For some reported SiO x /C composites, the rate performance are tested at current densities lower than 2 A g À1 , and their capacities decrease sharply with the increase of current density. Some SiO x /C composites deliver much higher capacities than SiO x /NC-2 at 0.1 and 0.2 A g À1 , but at about 3.2 A g À1 , their discharge capacities are lower than that of SiO x /NC-2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further confirm the advantages in the kinetics of the electrochemical process of the py-B-CNTs film, EIS measurement was carried out on the py-B-CNTs and CNTs (Figure 4E). It is observed that the Nyquist plots of both materials consist of a depressed semicircle in the high-frequency region and a linear Warburg part in the low frequency region, attributed to charge-transfer resistance and Li-ion diffusion in CNTs network structure, respectively (Sang et al, 2018). Specifically, an equivalent circuit was fitted as shown in the inset of Figure 4E.…”
Section: Resultsmentioning
confidence: 99%